ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI DAUN Garcinia dulcis (Roxb.)Kurz. - , HADY ANSHORY T, Prof. Dr. Subagus Wahyuono, M.Sc., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bacterial infection is a disease with a high incidence. On the other side, bacterial resistance to antibiotics are rising, so is needed to find a new anti-infective agents. Garcinia dulcis (Roxb.) Kurz. is one of the medicinal plants are reported to contain antibacterial compounds in flowers, fruits, seeds, bark and roots. However, an antibacterial compound from the leaves has not been reported, therefore this study aimed to isolate the antibacterial compounds from the G.dulcis leaves and determine antibacterial activity and chemical structure description. Method of Isolation of antibacterial compound from the G. dulcis leaves was directed by bioassay against Staphylococcus aureus. Extraction was done by maceration method using washbenzen and continued with methanol solvents. Washbenzen extracts were then separated by liquid-liquid partition technique (n-hexane: ethanol 70%). The bottom layer fractions (ethanolic fraction) were separated using vacuum liquid chromatography with a mixture solvent of n-hexane and ethyl acetate with various comparisons. The fraction with the highest antibacterial activity were separated by preparative thin layer chromatography using n-hexane : acetone (4:1 v/v). Purity test of the isolate was performed by multi-system eluent and two-dimensional TLC. Minimal Inhibitory Concentration (MIC) and MBC of isolates were tested by the microdilution method against S. aureus, S. epidermidis, S. mutans, E. coli, and Bacillus spp bacteria. Identification of the isolatâs chemical structure was conducted by spectroscopy method (UV, IR, GC-MS, and 1H-NMR). Garcinia dulcis leaves isolates has a high antibacterial activity against S. aureus, S. mutans, and Bacillus spp bacteria with MIC/MBC value of to 78.13 ïg/ml, while the antibacterial activity against S. epidermidis was lower with MIC and MBC values of 312.5 and 625 ïg/ml. The lowest activity was found against E. coli bacteria with MIC and MBC values of 1250 and 2500 ïg/ml, respectively. Based on spectral data UV, IR, MS, and 1H-NMR suggested that the chemical structures of the isolates were terpenoid group.